2017
DOI: 10.1186/s12986-017-0212-4
|View full text |Cite
|
Sign up to set email alerts
|

Milk disrupts p53 and DNMT1, the guardians of the genome: implications for acne vulgaris and prostate cancer

Abstract: There is accumulating evidence that milk shapes the postnatal metabolic environment of the newborn infant. Based on translational research, this perspective article provides a novel mechanistic link between milk intake and milk miRNA-regulated gene expression of the transcription factor p53 and DNA methyltransferase 1 (DNMT1), two guardians of the human genome, that control transcriptional activity, cell survival, and apoptosis. Major miRNAs of milk, especially miRNA-125b, directly target TP53 and complex p53-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 180 publications
(201 reference statements)
2
41
0
1
Order By: Relevance
“…Recent translational research evidenced that Western diet (hyperglycaemic carbohydrates and milk consumption) reduces the activity of transcription factor p53, which has been identified as being involved in the pathogenesis of acne and prostate cancer . Moreover, epidemiological findings underlined a correlation between acne in late adolescence and increased risk of prostate cancer which may potentially improve translational evidence for a relationship between dairy products and acne …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent translational research evidenced that Western diet (hyperglycaemic carbohydrates and milk consumption) reduces the activity of transcription factor p53, which has been identified as being involved in the pathogenesis of acne and prostate cancer . Moreover, epidemiological findings underlined a correlation between acne in late adolescence and increased risk of prostate cancer which may potentially improve translational evidence for a relationship between dairy products and acne …”
Section: Resultsmentioning
confidence: 99%
“…49,50 Recent translational research evidenced that Western diet (hyperglycaemic carbohydrates and milk consumption) reduces the activity of transcription factor p53, which has been identified as being involved in the pathogenesis of acne and prostate cancer. 51 Moreover, epidemiological findings underlined a correlation between acne in late adolescence and increased risk of prostate cancer which may potentially improve translational evidence for a relationship between dairy products and acne. 52 But, even though there are more and more elements confirming the relationship between acne and dairy products, to date there is no consensus concerning the role of fat levels in dairy products in the physiopathology of acne.…”
Section: Nutrition Factors Potentially Impacting On Acnementioning
confidence: 99%
“…First, only four cohort studies included in our meta-analysis, which limited the further subgroup analysis by study design. [44][45][46] Intriguingly, it was reported that the mortalityand bone fracture-increasing effects of milk intake had only been detected in relation to intake of pasteurized milk but not to fermented dairy products such as yogurts or cheeses. Second, our study was also limited by the self-reported diagnosis of acne as well as the ambiguous diagnostic criteria for acne in several included studies, both of which could result in a potential mis-validation of acne status and a recall and selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA hsa‐miR‐148a‐3p is consistently the most abundant microRNA in breast milk, most likely because of its importance for lactation and its enrichment in mammary gland cells (Chen et al., ; Do, Dudemaine, Li, & Ibeagha‐Awemu, ; Gu et al., ; Muroya et al., ). It is then with little surprise that this microRNA is the most studied milk microRNA (Benmoussa et al., ; Golan‐Gerstl et al., ; Melnik, ; Melnik & Schmitz, , ; Simpson et al., ; van Herwijnen et al., ). Other less‐expressed microRNAs have nevertheless been investigated in breast milk, like the immunity‐related microRNAs hsa‐miR‐223 or hsa‐miR‐146a (Iannaccone et al., ; Liao et al., ; Perri et al., ; van Herwijnen et al., ).…”
Section: Micrornas In Milkmentioning
confidence: 99%
“…Most interestingly, the major microRNAs found in these milks often overlap with human milk microRNAs, suggesting a conserved evolutive process that leads to the release of specific milk mi-croRNAs (Melnik, 2017;Melnik et al, 2016;Melnik & Schmitz, 2017a;van Herwijnen et al, 2018;Zempleni et al, 2016;Zempleni, Baier, Howard, & Cui, 2015b). Considering domestic animal-derived milks that are part of human consumption (cow and goat), it is interesting to note that the top 10 microRNAs found in these two species (Table 1 and Figure 1B), is quite close to human milk microRNA profiles ( Figure 1A; Melnik, 2017;Melnik et al, 2016;Melnik & Schmitz, 2017a;van Herwijnen et al, 2018;Zempleni et al, 2016;Zempleni, Baier, & Hirschi, 2015a).…”
Section: Micrornas Found In Milk From Other Speciesmentioning
confidence: 99%